Relationship between circadian disruption and mood instability in shift workers - Almughamsi, Reyouf Abdulsalam; Al Zaqan, Abdulmohsen Ahmed; Hamid, Sana Salah; Almadani, Mohammed Salman; Alasmari, Ali Mohammed; Ageel, Salman Abdulaziz; Alotaibi, Hissah Muthyib; Mahmoud, Waseem Mazen; Aseeri, Thekra Ali; Alshammari, Omar Mohammed (International Journal Of Community Medicine And Public Health, 2026)
Shift work has become a structural necessity in modern economies, yet its impact on mental health remains a growing concern. Circadian disruption, a core consequence of working non-standard hours, has been consistently linked to mood instability. This misalignment between internal biological rhythms and externally imposed work schedules affects key physiological systems involved in emotional regulation, including sleep-wake cycles, hormonal rhythms, and neurotransmitter activity. Disturbed sleep architecture, altered cortisol patterns, and impaired serotonergic function all contribute to heightened vulnerability to mood disorders such as depression, anxiety, and emotional lability among shift workers. The relationship between circadian misalignment and mood is not uniform across individuals. Genetic predispositions, diurnal preference, social environment, and occupational conditions play a substantial role in modulating emotional outcomes. Evening chronotypes may adapt more efficiently to night shifts, while certain polymorphisms in circadian genes increase sensitivity to rhythm disruption. Social support and perceived control over work schedules further influence psychological resilience in these populations. Clinical interventions targeting circadian health have shown efficacy in improving emotional outcomes. Light therapy, melatonin, and behavioral strategies such as cognitive behavioral therapy for insomnia have demonstrated benefits in regulating both sleep and mood. Preventive measures, including forward-rotating shift schedules, extended recovery periods, and fatigue risk management systems, also contribute to mitigating psychological harm. Addressing mood instability in shift workers requires a multidimensional approach that considers biological rhythms, individual risk modifiers, and systemic workplace design.